Rancang Bangun Aplikasi Inventaris Barang Berbasis Web Pada SMAN 1 Padang Ganting - Amri, Alwi Dwi; Slamet, Legiman; Delianti, Vera Irma; Darni, Resmi (Universitas Negeri Padang, 2023)
The rapid advancement of technology has significantly enhanced information management capabilities in various institutions, presenting opportunities for developing technology-based systems, particularly in information technology and data processing. Efficient information systems are crucial for progress in both business and educational sectors. A school inventory management system is one such application designed to manage inventory data more efficiently and systematically. State Senior High School 1 Padang Ganting, a high school under the Ministry of Education and Culture, currently uses a manual method for inventory management, leading to data duplication, data loss, and inefficiency. To address these issues, this research proposes developing a web-based inventory management application aimed at improving data management, speeding up information access, and enhancing service quality within the school. The development methodology adopted is the waterfall model, which involves structured phases from requirement analysis to system maintenance. The system design utilizes PHP with the Laravel framework, JavaScript, Laragon as the web server, MySQL as the DBMS, and Visual Studio Code as the editor. This study aims to design and build a web-based inventory management application for State Senior High School 1 Padang Ganting, providing a structured and easily accessible system.